Deep Learning for Medical Decision Support Systems : Foreword - Marmolejo Saucedo, José Antonio; Litvinchev, Igor (Springer Singapore, 2021)
In this book, different medical data handling techniques are used to develop medical decision support systems in the context of diagnosis perspective. The objective is to use all available information in the decision-making to improve the quality of medical care and to help less experienced doctors in diagnostics.
Foreword : Deep Learning for Medical Decision Support Systems